Quantifying carbon pool in ex-mining lake-converted constructed wetlands of Paya Indah Wetlands, Selangor, Malaysia - Jamion, Nurul' Ain; Lee, Khai Ern *; Mokhtar, Mazlin *; Goh, Thian Lai (Springer, 2024)
Ex-mining lake-converted constructed wetlands play a significant role in the carbon cycle, offering a great potential to sequester carbon and mitigate climate change and global warming. Investigating the quantity of carbon storage capacity of ex-mining lake-converted constructed wetlands provides information and justification for restoration and conservation efforts. The present study aims to quantify the carbon pool of the ex-mining lake-converted constructed wetlands and characterise the physicochemical properties of the soil and sediment. Pearson’s correlation and a one-way ANOVA were performed to compare the different sampling stations at Paya Indah Wetland, Selangor, Malaysia. An analysis of 23 years of ex-mining lake-converted constructed wetlands of Paya Indah Wetlands, Selangor, Malaysia, revealed that the estimated total carbon pool in soil and sediment accumulated to 1553.11 Mg C ha−1 (equivalent to 5700 Mg CO2 ha−1), which translates to an annual carbon sink capacity of around 67.5 Mg C ha−1 year−1. The characterisation showed that the texture of all soil samples was dominated by silt, whereas sediments exhibited texture heterogeneity. Although the pH of the soil and sediment was both acidic, the bulk density was still optimal for plant growth and did not affect root growth. FT-IR and WDXRF results supported that besides the accumulation and degradation of organic substances, which increase the soil and sediment carbon content, mineral carbonation is a mechanism by which soil and sediment can store carbon. Therefore, this study indicates that the ex-mining lake-converted constructed wetlands of Paya Indah Wetlands, Selangor, Malaysia have a significant carbon storage potential.